2024
DOI: 10.1523/eneuro.0412-23.2024
|View full text |Cite
|
Sign up to set email alerts
|

Human Foot Outperforms the Hand in Mechanical Pain Discrimination

Kevin K. W. Ng,
Odai Lafee,
Otmane Bouchatta
et al.

Abstract: Tactile discrimination has been extensively studied, but mechanical pain discrimination remains poorly characterised. Here, we measured the capacity for mechanical pain discrimination using a two-alternative forced choice paradigm, with force-calibrated indentation stimuli (Semmes-Weinstein monofilaments) applied to the hand and foot dorsa of healthy human volunteers. In order to characterise the relationship between peripheral nociceptor activity and pain perception, we recorded single-unit activity from myel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The recently discovered Aβ nociceptors in human skin are particularly well-suited to signal percepts and responses requiring rapid transmission of nociceptive information from the periphery [23, 25, 41]. In microneurography, intraneural stimulation of Aβ nociceptors produces painful percepts at the same current intensities where intraneural stimulation of Aβ tactile afferents produces nonpainful percepts [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently discovered Aβ nociceptors in human skin are particularly well-suited to signal percepts and responses requiring rapid transmission of nociceptive information from the periphery [23, 25, 41]. In microneurography, intraneural stimulation of Aβ nociceptors produces painful percepts at the same current intensities where intraneural stimulation of Aβ tactile afferents produces nonpainful percepts [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that human skin is equipped with a specific class of high-threshold mechanoreceptors with Aβ conduction velocities. These receptors encode noxious mechanical stimuli and produce painful percepts when selectively activated through low-current intraneural stimulation [23][24][25]. This discovery raises the question of whether Aβ inputs contribute to painful NWR signaling in humans.…”
Section: Introductionmentioning
confidence: 99%